2014
DOI: 10.1095/biolreprod.114.120220
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Subunit Aalpha of PP2A Is Essential for Female Meiosis and Fertility in Mice1

Abstract: Ppp2r1a encodes the scaffold subunit Aalpha of protein phosphatase 2A (PP2A), which is an important and ubiquitously expressed serine threonine phosphatase family and plays a critical role in many fundamental cellular processes. To identify the physiological role of PP2A in female germ cell meiosis, we selectively disrupted Ppp2r1a expression in oocytes by using the Cre-Loxp conditional knockout system. Here we report for the first time that oocyte-specific deletion of Ppp2r1a led to severe female subfertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…45 The loss of scaffold subunit PP2A-Aa in mouse oocytes compromised spindle shape and cytokinesis in meiosis II without affecting spindle formation during meiosis I. 24 Comparing with our results, the scaffold and catalytic subunits of PP2A appear to play different specific roles during meiotic maturation. Another possibility is that PP2A-Ab functionally compensates for PP2A-Aa during oocyte meiosis I.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formasupporting
confidence: 69%
See 4 more Smart Citations
“…45 The loss of scaffold subunit PP2A-Aa in mouse oocytes compromised spindle shape and cytokinesis in meiosis II without affecting spindle formation during meiosis I. 24 Comparing with our results, the scaffold and catalytic subunits of PP2A appear to play different specific roles during meiotic maturation. Another possibility is that PP2A-Ab functionally compensates for PP2A-Aa during oocyte meiosis I.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formasupporting
confidence: 69%
“…Previous studies showed that inhibition of PP2A by OA or specifically deleting scaffold PP2A-Aa facilitates GVBD in oocytes, 19,24,37,38 and PP2Acb may play a key role in the meiotic arrest of oocytes. 18,19 In our study, the loss of PP2Acs did not significantly affect GVBD kinetics in oocytes under normal culture condition.…”
Section: Pp2a Is Essential For Chromosome Alignment and Spindle Formamentioning
confidence: 97%
See 3 more Smart Citations